Detecting and identifying pathogens and antagonistic bacteria associated with Ginkgo biloba leaf spot disease - Shen, Huoyun; Li, Xiyang; Li, Zilong (Frontiers in Microbiology, 2024)
Background: Leaf spot disease severely impacts Ginkgo biloba (G. biloba) yield and quality. While microbial agents offer effective and non-toxic biological control for plant diseases, research on controlling leaf spot disease in G. biloba is notably scarce.The pathogenic fungi were isolated and purified from diseased and healthy leaves of G. biloba, Subsequent examinations included morphological observations and molecular identification via PCR techniques. A phylogenetic tree was constructed to facilitate the analysis of these pathogenic fungi, and Koch's postulates were subsequently employed to reaffirm their pathogenic nature. The antagonistic experiment was employed to select biocontrol bacteria, and subsequently, the isolated biocontrol bacteria and pathogenic fungi were inoculated onto healthy leaves to assess the inhibitory effects of the biocontrol bacteria.: Two pathologies responsible for the leaf spot disease on G. biloba were identified as Botryosphaeria dothidea and Neofusicoccum parvum via the analysis of phylogenetic tree and the application of Koch's Postulates. Additionally, we isolated two strains of biocontrol bacteria, namely Bacillus velezensis and Bacillus amyloliquefaciens. Their average inhibitory zones were measured at 4.78 cm and 3.46 cm, respectively. The inhibition zone of B. velezensis against N. parvum was 4 cm. B. velezensis showed a stronger inhibitory effect compared to B. amyloliquefaciens on the development of lesions caused by B. dothidea via leaf culture experiment. Conclusion: This research reports, for the first time, the presence of B. dothidea as a pathogenic fungus affecting G. biloba. Moreover, the biocontrol bacteria, B. velezensis and B. amyloliquefaciens, exhibited the capability to effectively inhibit the growth and reproduction of B. dothidea, indicating their promising potential as environmentally friendly biocontrol resources.